Visualization of 2-D and 2.5-D spatial data in arc/info environment - Abdul Rahman, Alias; Tan, Lye Siang (Fakulti Ukur dan Harta Tanah, 1994)
Paper maps were traditionally used to portray terrain reliefs. IWs was the only known method to represent the terrain and other terrain features, e.g. by using contour lines, hachures, spot heights, etc. This paper attempts to describe some of the favourable and effective techniques for visualizing terrain from 2.5-D spatial datasets (i.e. planimetric data with height as an attribute) such as contour lines. The 2-D datasets is draped on top of the generated DTM surface using TIN Surface Module of Arc/Info Rev. 6 software (workstation-based). Some realistic three-dimensional models are presented.